Transthoracic Lung node biopsy under navigation of C-arm based universal angiographic complex - I. S. Baryshnikov; A. O. Egorova; Dmitry Alexandrovich Polezhaev (Вестник хирургии имени И.И. Грекова)
The objective was to study the possibilities of using the C-arm based universal angiographic complex as a navigation system in transthoracic biopsies of pulmonary nodules.Methods and materials. The study is based on the data of 60 patients with lesion size from 10 to 103 mm (mean 51 mm) have been underwent the transthoracic biopsy using C-arm based universal angiographic complex navigation. A total of 69 biopsies were performed (60 primary, 9 repeated). The procedure was made with local anesthesia in an interventional operating room. The postoperative observation time was 1 day.Results. A tissue sample was got in all cases. As a result of a biopsy, a malignant tumor was confirmed in 70 % of patients (42 people). At the primary biopsy, data for the malignant process were not obtained in 30 % (18 people), however, in half of the cases (9 people), the diagnosis of a malignant tumor was confirmed after repeated biopsy. The radiation dose received by the patient was 2.05-60.50 mSv (mean 13.94mSv), which is comparable to the radiation dose in traditional CT navigation and less than the average dose of radiation obtained using CT fluoroscopy. Sensitivity, specificity, accuracy were 82.35, 100 и 35 % respectively. Complications occurred in 18 cases (26.09 %). There was no need to perform interventions under general anesthesia. Transfer of patients to the intensive care unit was not required. No fatal complications occurred.Conclusion. This navigation system is safe and effective and can be used routinely.